Tracing the History of Trans and Gender Variant Filmmakers - Horak, Laura (Spectator: The University of Southern California Journal of Film & Television, 2017)
Most writing on transgender cinema focuses on representations of trans people, rather than works made by trans people. This article surveys the history of trans and gender variant people creating audiovisual media from the beginning of cinema through today. From the professional gender impersonators of the stage who crossed into film during the medium’s first decades to selfidentified transvestite and transsexual filmmakers, like Ed Wood and Christine Jorgensen of the mid-twentieth century, to the enormous upsurge in trans filmmaking of the 1990s, this article explores the rich and complex history of trans and gender variant filmmaking. It also considers the untraceable gender variant filmmakers who worked in film and television without their gender history becoming known and those who made home movies that have been lost to history.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 5-Créateur.rice LGBTQ+; _Nettoyé

Cross-Dressing and Transgender Representation in Swedish Cinema, 1908–2017 - Horak, Laura (European Journal of Scandinavian Studies, 2017)
Today’s explosion of Swedish films made by and about transgender people is sometimes considered in a vacuum. This article explores the long history of cross-gender performance in Swedish cinema and the relationship of these new films to older traditions. In this article, I will outline the contours of cross-gender performance in Swedish films from the 1908 to today, using some exemplary films to display the variety of styles, genres, and meanings that can be found: the short dance film Dances Through the Ages ( Skilda tiders danser , Walfrid Bergström, 1909); the swashbuckler Lasse-Maja (Gunnar Olsson, 1941); the romantic comedy Up With Little Märta ( Fram för Lilla Märta , Hasse Ekman, 1945); the dramatic art film The Magician ( Ansiktet , Ingmar Bergman, 1958); the recent romantic comedy Cockpit (Mårten Klingberg, 2012); and the trans art film Everything Falls Apart ( Nånting måste gå sönder , Ester Martin Bergsmark, 2016). I will show that the two main shifts in Swedish cinema’s representation of cross-gender performance occurred in the mid-1950s and in the 1990s, due to social changes and changes in the structure of the Swedish film industry. In Swedish cinema, as elsewhere, cross-dressing has never meant any one thing, so we must attend to the specific contexts of its expression in order to understand what it meant.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé